The role of lipoprotein a in cardiac risk stratification and evaluation of hypolipemizing treatment - Maria Maciąg; Karolina Garbacz; Małgorzata Pasztelan; Aleksandra Marczak; Julia Krawczuk vel Walczuk; Jarosław Pulikowski; Małgorzata Słaboń; Maciej Sobczyk; Aleksandra Muca; Joanna Baran (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose Cardiovascular diseases are one of the most common causes of death. Due to their popularity and the costs they generate, they are a significant problem. One of the cardiovascular risk factors is the level of lipoprotein(a). Lipoprotein (a) levels are not commonly used to stratify cardiovascular risk, but recommendations suggest that every adult should have them checked. The aim of this study is to discuss current knowledge about the role of lipoprotein (a) in cardiac risk stratification and evaluation of hypolipemizing treatment. Material and methods The PubMed database was used to review the literature. An electronic literature search was conducted, publication years were limited to 2018-2024. Three articles that did not meet this criterion due to their earlier publication dates were included because they served as important sources of information for this article. Keywords were used as search terms. Conclusion Based on the available data, the benefits of lowering lipoprotein(a) levels in the context of cardiovascular diseases cannot be confirmed. There is a need for further research into the role of lipoprotein (a) in stratifying cardiovascular risk, the benefits of lowering its levels, and specific therapeutic approaches for this disorder.